GROWTH, YIELD AND MINERAL CONTENT OF BROCCOLI INTERCROPPED WITH LETTUCE - E. Yildirim; M. Turan (Journal of Animal and Plant Sciences, 2013)
This study was conducted to determine the effect of intercropping with lettuce on growth, chlorophyll content, mineral content and yield of broccoli under field conditions during 2009 and 2010. The broccoli (Brassica oleracea L. var. italica) as a main crop was intercropped with leaf lettuce (Lactuca sativa L. var. crispa) as intercrop. The study was carried at University of Atatürk in Turkey. The experimental design was a randomised complete block design with three replications. Lettuce seedlings were planted in the middle of broccoli rows, both crops were also grown in pure stands as control. Results of this study indicated that intercropping systems compared to sole did not affect some growth characteristics and yield of broccoli except for weight per plant. Phosphorus (P), sulphur (S), iron (Fe), and manganese (Mn) content of broccoli leaves did not vary significantly depending on cropping systems. However, intercropping caused decrease in nitrogen (N), potassium (K), magnesium (Mg), calcium (Ca) and zinc (Zn) concentration compared to sole broccoli cropping. The study showed that broccoli based intercrop treatments might provide the highest total yield as well as productivity and profitability.
Keywords: intercropping; broccoli; lettuce; growth; yield; LER